2019
DOI: 10.1021/acssuschemeng.9b04772
|View full text |Cite
|
Sign up to set email alerts
|

Cs-Doped TiO2 Nanorod Array Enhances Electron Injection and Transport in Carbon-Based CsPbI3 Perovskite Solar Cells

Abstract: Carbon-based CsPbI 3 perovskite solar cells (CsPbI 3 C-PSCs) without hole-transporting materials have been attracting much attention because of their high stability. However, the electron transport layer (ETL) of TiO 2 mesoporous scaffolds has hindered electron transport. Herein, we solve the above problem by employing a Cs-doped TiO 2 (Cs-TiO 2 ) nanorod array as an ETL, which provides a direct and fast electron path. Cs doping well increases the free charge carrier density in the TiO 2 nanorod array to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 54 publications
(120 reference statements)
0
30
0
Order By: Relevance
“…This is more conducive to the carriers transfer from the absorber layer to the CTL layer and then to the electrode layer. So far, various elements (such as Cs, Sn, Cd, and so on) have been doped into the ETL layers to further improve their electrical properties 36,56,60‐64 . For instance, Li et al added the tantalum chloride to hydrothermal precursor solution to prepare Ta‐doped TiO 2 nanorods, 50 and the doping phenomenon was confirmed by the X‐ray diffraction (XRD) patterns (Figure 3B) and the elemental analysis of transmission electron microscopy (TEM) (Figure 3C).…”
Section: Ordered Array Structures For Etlmentioning
confidence: 99%
See 1 more Smart Citation
“…This is more conducive to the carriers transfer from the absorber layer to the CTL layer and then to the electrode layer. So far, various elements (such as Cs, Sn, Cd, and so on) have been doped into the ETL layers to further improve their electrical properties 36,56,60‐64 . For instance, Li et al added the tantalum chloride to hydrothermal precursor solution to prepare Ta‐doped TiO 2 nanorods, 50 and the doping phenomenon was confirmed by the X‐ray diffraction (XRD) patterns (Figure 3B) and the elemental analysis of transmission electron microscopy (TEM) (Figure 3C).…”
Section: Ordered Array Structures For Etlmentioning
confidence: 99%
“…So far, various elements (such as Cs, Sn, Cd, and so on) have been doped into the ETL layers to further improve their electrical properties. 36,56,[60][61][62][63][64] For instance, Li et al added the tantalum chloride to hydrothermal precursor solution to prepare Ta-doped TiO 2 nanorods, 50 and the doping phenomenon was confirmed by the X-ray diffraction (XRD) patterns ( Figure 3B) and the elemental analysis of transmission electron microscopy (TEM) ( Figure 3C). By optimizing doping solubility, the conduction band (CB) of optimal Ta-doped TiO 2 had a 0.05 eV downshift compared to the pristine TiO 2 .…”
Section: D Ordered Array Structured Etlmentioning
confidence: 99%
“…It was found that the Cs + ‐doped ZnO with an optimal doping concentration of 5% obtained excellent transparency, proper band alignment, high NP crystallinity, large conductivity, and more smooth film morphology owing to surface defects of the ZnO were effectively passivated. Later, Liu et al [ 167 ] synthesized the Cs + ‐doped TiO 2 nanorod array as ETLs in CsPbI 3 ‐based PSCs to enhance charge injection and transport efficiency. They discovered that the incorporation of Cs + into TiO 2 multiplies the free charge density greatly, upshifts CB, and fills remarkably pore of the perovskite film, which results in an increased PCE from 5.8% to 9.5%.…”
Section: Doping Of Semiconductor Oxides Etlsmentioning
confidence: 99%
“…[125][126][127] Bilayer structure and new materials are two common ways to improve the properties of CTL. [38,[128][129][130] Ethanol solution of thiourea was used to obtain the ZnO-ZnS ETL, the CsPbI 3 PSC with a PCE of 16.9%, and the large-area module (active area is 8 cm 2 ) with a PCE of 11.8% were prepared. [131] Bai et al introduced a SnO 2 /ZnO bilayer ETL to CsPbI 3 PSCs.…”
Section: Charge Transfer Layermentioning
confidence: 99%